2018
DOI: 10.5539/gjhs.v10n5p78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Special Cognitive-Behavioral Intervention on Commitment to Exercise and Mental Health

Abstract: Background: Although most people are aware of the advantages of physical exercise, they have failed to commit to it. This forms justification for this intervention.Objectives: In this study, the effect of special cognitive-behavioral intervention on commitment to exercise and mental health in adults was investigated by controlling the role of the commitment-to-exercise variable. Methods:The statistical population for this study comprised 635 employees with over 10 years' professional experience: 235 were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Cronbach α Coefficient values of the internal consistency for ALES including 12 items were analyzed and it was measured as 0.850. The third one was Adherence to Physical Activity Scale (APAS), It was developed by (Derakhshanpour, 2016). The scale consists of 11 items and three sub-dimensions.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach α Coefficient values of the internal consistency for ALES including 12 items were analyzed and it was measured as 0.850. The third one was Adherence to Physical Activity Scale (APAS), It was developed by (Derakhshanpour, 2016). The scale consists of 11 items and three sub-dimensions.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The statistical population of the study consisted of 565 individuals who do exercise and physical activity in public parks of Mashhad city in 2021. Quality of Life scale (QLS, SF26), Adult Life Expectancy Scale ((ALES), Snyder et al, 1991), and Adherence to Physical Activity Scale ((APAS) Derakhshanpour et al, 2016), were used as data collection tools in this research. The results showed that there was almost moderate to strong positive correlation between quality of life with life expectancy, factor thinking and strategic thinking.…”
mentioning
confidence: 99%
“…Commitment and adherence to physical activity and exercise was measured with the Adherence to Physical Activity Questionnaire [7]. The items are enthusiasm for exercise, exercise intensity and frequency, reinforcement, and disruption.…”
Section: Adherence To Physical Activitymentioning
confidence: 99%